The impact of revascularizatıon vıa stenting on left ventricular ejection fraction ın patients with myocardial infarction (CARDIOLOGY OF UZBEKISTAN, 2025)
Aim. To evaluate the one-year dynamic effect of complete or incomplete revascularization on left ventricular ejection fraction (LVEF) in patients with a history of myocardial infarction (MI) who have preserved or mildly reduced LVEF. Materials and methods. The study included 270 patients with a history of MI. All patients underwent transthoracic echocardiography and coronary angiography (CAG) based on clinical examination findings. Depending on the number of affected atherosclerotic coronary vessels and the extent of stenting performed, patients were divided into three groups: Complete revascularization (CR) (n=115), Incomplete revascularization (IR) (n=94), and No revascularization (NR) (n=61). After the procedure, all patients were discharged with standard treatment. After one year, follow-up echocardiographic assessment of LVEF was performed. Results. In the CR group, LVEF increased significantly from 54.0 [47.0; 59.7] to 55.7 [46.9; 61.4] (p = 0.017). In the IR group, LVEF increased from 53.9 [43.7; 56.4] to 55.7 [46.9; 61.4], but the change was not statistically significant (p = 0.458). In the NR group, LVEF decreased from 50.7 [45.0; 56.3] to 48.2 [41.8; 54.3] (p = 0.011). No statistically significant differences were observed between groups in terms of diastolic function parameters of the left ventricle. Conclusion. In post-infarction patients, complete anatomical revascularization of affected coronary arteries via stenting has a significantly positive impact on the improvement of LVEF.